Anthropometry of Romany school age children from eastern Slovakia - Duranková Silvia; Csanády Alexander; Ružbarská Ingrid (Sciendo, 2023)
Study aim: The aim of the study was to perform an anthropometric analysis of children of the minority population of younger school age from eastern Slovakia.